Synthesis, Preliminary Anticonvulsant (Electro-Shock) and Acute Oral Toxicity Screening of Substituted-3-Acetyl-2-(substitutedphenyl)-4-methylbenzo[b][1,4]thiazepin-5(2H)-yl)-1-(substitutedphenyl)propan-1-one (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The current research aimed to synthesize a novel series of 5-substituted mannich bases using the substitution at 5th position at which the hydrogen atom was replaced by two different substituents, p-nitroacetophenone and p-chloroacetophenone having significant anticonvulsant activity. A novel series of substituted-3-acetyl-2-(substitutedphenyl)-4-methylbenzo[b][1,4]thiazepin-5(2H)-yl)-1-(substitutedphenyl)propan-1-one (6a-6t) were synthesized and evaluated for pharmacological activity. A total of 20 compounds, were synthesized by conventional methods and the purity of synthesized compounds were confirmed by melting point and thin layer chromatography (TLC) analysis. Fourier transform infrared (FTIR), proton nuclear magnetic resonance (1H-NMR), mass and elemental analysis characterized the structures of lead compounds. All the novel synthesized compounds (6a-6t) were preliminarily screened by anticonvulsant activity by maximum electroshock induced seizure against phenytoin as a standard drug at a 30 mg/kg dose. In the results of the spectral study, all the compounds showed characteristic peaks in FTIR and 1H-NMR spectroscopy. Compounds containing chlorine moiety show [M+2]+ peak in mass spectrum. In this study all the novel synthesized compounds showed significant anticonvulsant activity. The most significant synthesized compound 3-acetyl-2-(3-chlorophenyl)-4-methylbenzo[b][1,4]thiazepin-5(2H)-yl)-1-(4-chlorophenyl)propan-1-one (6e) found as a primary class of anticonvulsants that have shown practically identical anticonvulsant action with uniquely lower neurotoxicity. Further, the preliminary safety profile of the most potent significant compound (6e) was screened for 'acute oral toxicity' as per organisation for economic co-operation and development (OECD) guidelines, in total fourteen days of observation the normal behavior of animals suggest that compound (6e) was safe and non-toxic in nature. This study suggested further modification and improvement in the field of anticonvulsants drug development.